A Heuristic Lot Size Reorder Point Model for Decaying Inventories - Nahmias, Steven; Wang, Shan Shan (Management Science, 1979)
In this paper we consider the problem of finding a “good” lot size and reorder point policy for an inventory which is subject to continuous exponential decay. Examples of decaying inventories include alcohol, certain types of food items, and radioactive materials. The method of analysis is an approximate approach which parallels that of Hadley and Whitin in the no-decay case. To evaluate the effectiveness of the approximation, a computer simulation is developed to estimate and evaluate the best (Q, r) policy. A comparison of the approximate and simulated policies is made for a total of thirty test cases resulting in a maximum cost error of only 2.77%.